The effectiveness of development skills plan framework for learning disabilities children: a systematic literature review - Zulkifli, Zahidah; Mat Surin, Ely Salwana; Abdul Rahman, Abdul Wahab (IEEE, 2018)
The purpose of this paper is to investigate the evidence related to the effectiveness of the current Development Skills Plan Framework (DSPF) for Learning Disabilities (LD) Children in the context of Autistic Education System. LD means intellectual capabilities that do not conform with biological age. The paper opted for a systematic literature review (SLR) survey on investigating the factors that affect the effectiveness of Development Skills Plan Framework been used for LD Children within Autistic Education System. The practices of studies for this SLR are between 2010 and 2018. The study includes a set of 8 papers from among 157 retrieved papers published in SCOPUS-indexed journals. Results showed that children literacy skill was the factor that affected the Effectiveness of Development Skills Plan Framework the most. The analysis showed that children literacy skill helps to improve the LD children which is the chief developmental milestone with lifelong consequences. 7 important factors lead to the effectiveness of Development Skills Plan Framework: health, literacy skill, social and life skills, environments, mentorship, behavior, and technology. These 7 factors are important to be used for modeling a DSPF for LD children for future works